2009
DOI: 10.1016/j.jpeds.2008.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Child Abuse Risk from Emergency Department Use

Abstract: Objective-To examine whether pre-abuse rates and patterns of emergency department (ED) visits between children with supported child abuse and age-matched controls are useful markers for abuse risk.Study design-A population-based case-control study using probabilistic linkage of four statewide data sets. Cases were abused children <13 years, identified between 1/1/01-12/31/02. For each case, a birth date matched population-based control was obtained. Outcome measures were rate ratios of ED visits in cases compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 27 publications
5
46
0
2
Order By: Relevance
“…This problem would be avoided if health and social care data were linked to create anonymised data for analyses. Such data could provide powerful insights into the health problems faced by maltreated children seen by social care,19 20 and into the pathways from health into social care 2123. Without follow-up data, our inferences about the sources of such variation need to be cautious as recording of maltreatment in HES reflects processes at three levels: recognition by clinicians, recording in hospital notes and the quality of information capture by hospital coders and their approach to coding.…”
Section: Discussionmentioning
confidence: 99%
“…This problem would be avoided if health and social care data were linked to create anonymised data for analyses. Such data could provide powerful insights into the health problems faced by maltreated children seen by social care,19 20 and into the pathways from health into social care 2123. Without follow-up data, our inferences about the sources of such variation need to be cautious as recording of maltreatment in HES reflects processes at three levels: recognition by clinicians, recording in hospital notes and the quality of information capture by hospital coders and their approach to coding.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Guenther et al stated that ''children who went onto have supported neglect or physical abuse did not have more injury visits than control subjects'' and that their study ''did not find any 'red flags' from either the frequency or pattern of a child's ED visits, which would allow early identification of children at risk for abuse by the ED physician'' [10].…”
Section: Discussionmentioning
confidence: 95%
“…These children have a higher use of EDs compared with the general population. 20 Although it is unreasonable to treat every patient as if they are being abused, it is the role of EPs to keep a high index of suspicion. There have been numerous attempts at developing appropriate criteria for ED screening of abuse, including reminder systems, scheduled education, and automatic screening based on risk factors.…”
Section: High-risk Chief Complaintsmentioning
confidence: 99%
“…There have been numerous attempts at developing appropriate criteria for ED screening of abuse, including reminder systems, scheduled education, and automatic screening based on risk factors. 20,21 Although observational studies suggest that these may be useful, none have been shown to be sufficiently accurate or reproducible. [22][23][24][25] A brief introspection of whether the child is being abused is often enough of a consideration, but there are several chief complaints that deserve further investigation.…”
Section: High-risk Chief Complaintsmentioning
confidence: 99%